« Le Paradis de Zahra » : le grand cimetière de Téhéran entre pratiques populaires et rationalité étatique - Parsapajouh, Sepideh (Revue des mondes musulmans et de la Méditerranée, 2019)
Located south of Tehran, the Behesht Zahra Cemetery (Zahra Paradise), covers 700 hectares. It is the largest cemetery in Iran. With an average of 200 funerals per day the Cemetery requires efficient funeral management services. Since the 1979 Islamic Revolution and the deadly war against Iraq (1980-1988), this cemetery has become emblematic of the country's contemporary history, where the construction of traditional and revolutionary religious and political identities is at stake. Drawing on ethnographic data collected in the field over recent years, this article proposes a reflection on the complex articulations between the rationality of a modern state, albeit one that is religiously inspired, the ritual norms defined by religious scholars and scrupulously respected by a centralized funerary administration, and the daily practices of simple believers who, attached to the cult of the dead often observe with more passion than reason.